THE ABILITY OF POSTPARTUM PRIMIPARA ADOLESCENT MOTHERS IN BREASTFEEDING NEWBORN BABY AT UPT BLUD PUSKESMAS NARMADA WEST LOMBOK, THE PROVINCE OF WEST NUSA TENGGARA IN 2017 - Baiq Yuni Fitri Hamidiyanti; Mutiara Rahmawati Suseno (Jurnal Kesehatan Prima, 2018)
Abstract: A transition become parents will be difficult for teenage parents, a teenage primipara mothers in the first week are still not ready to accept her new duties as a mother. Primipara mothers often have feelings of inadequacy and inability to perform baby care skills, such as breastfeeding or breastfeeding. This study aimed to determine the ability of postpartum primipara adolescent mothers in breastfeeding newborn baby. Type of observational study with cross sectional design. The study population was all postpartum primipara maternal adolescents at Puskesmas Narmada from May to July 2017, sampling technique used purposive sampling and the number of samples obtained as many as 40 respondents. The statistical test used is linear regression test. The results showed that there was influence of the ability to breastfeed newborns on third day with infant weight on third day, with p = 0.000 or p <0,05, with regression coefficient value equal to R = 0,576. Results on the seventh day was the effect of the ability to breastfeed newborns on seventh day with infant weight on seventh day, with p = 0.000 or p <0.05. The conclusion of the study there is a significant influence of the ability to breastfeed newborns with the growth of newborn weight.Keywords: Ability, Primipara Adolescent, Breastfeeding Newborn Baby.